1991
DOI: 10.1039/p19910002603
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (±)-2′,3′-didehydro-2′,3′-dideoxy nucleosides via a modified Prins reaction and palladium(0) catalysed coupling

Abstract: Cyclopentenyl allylic acetates have been prepared in diastereoisomerically enriched form by modification of the Prins reaction. Palladium(o) catalysed coupling between these allylic acetates and a heteroaromatic base provides a highly convergent and direct route for synthesising car bocycl i c 2',3' -d ide h y d ro -2',3'd ideoxy n ucleosides. The met hod is exem pl if ied by the c o u pl i ng reaction with adenine which yields ( & ) -2',3'-didehydro-2',3'-dideoxyaristeromycin 5'-O-acetate 22 in 50% yield. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Palladium(0) derivatives are known to catalyze N ‐allylation reactions of free (NH)‐imidazoles with allylic electrophiles 117120. In 1991, Lindell and co‐workers found that imidazole undergoes Pd(PPh 3 ) 4 ‐catalyzed N‐ allylation by treatment with a diastereoisomerically enriched mixture of 3‐acetoxy‐4‐(acetoxymethyl)cyclopentene in THF in the presence of Et 3 N (Scheme ) 117…”
Section: Functionalization Of Imidazoles At the N‐1 Positionmentioning
confidence: 99%
“…Palladium(0) derivatives are known to catalyze N ‐allylation reactions of free (NH)‐imidazoles with allylic electrophiles 117120. In 1991, Lindell and co‐workers found that imidazole undergoes Pd(PPh 3 ) 4 ‐catalyzed N‐ allylation by treatment with a diastereoisomerically enriched mixture of 3‐acetoxy‐4‐(acetoxymethyl)cyclopentene in THF in the presence of Et 3 N (Scheme ) 117…”
Section: Functionalization Of Imidazoles At the N‐1 Positionmentioning
confidence: 99%
“…Palladium-catalyzed allylation of a heterobase possessing a free NH position is one of the highly useful strategies for assembling carbocyclic nucleosides. 16 We have successfully used this method for the synthesis of carbocyclic nucleoside 41 from carboline 16a and cis-diacetate 32.…”
Section: Figurementioning
confidence: 99%
“…Carbocyclic nucleosides 37 and 39 were obtained according to the Mitsunobu protocol. 16 A soln of DEAD (8.9 mmol) in anhyd MeCN was added dropwise to a stirred, cooled soln (0°C) of a carbocyclic sugar (3.7 mmol).…”
Section: Compounds 37 and 39mentioning
confidence: 99%
“…The cis-diacetate 146 was readily prepared using a ptoluenesulfonic acid-catalyzed Prins reaction between cyclopentadiene and paraformadehyde in acetic acid: the reaction was not completely stereo-and regioselective, giving also the other three isomers [48]. Compound 146 and the corresponding deprotected diol are synthetically interesting because can be transformed into carbocyclic nucleoside derivatives [49].…”
Section: Prins Reaction In Synthesismentioning
confidence: 99%